2012
DOI: 10.3390/ijms13033703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylene Glycol Modification of TiO2 Nanoparticles on Cytotoxicity and Gene Expressions in Human Cell Lines

Abstract: Nanoparticles (NPs) are tiny materials used in a wide range of industrial and medical applications. Titanium dioxide (TiO2) is a type of nanoparticle that is widely used in paints, pigments, and cosmetics; however, little is known about the impact of TiO2 on human health and the environment. Therefore, considerable research has focused on characterizing the potential toxicity of nanoparticles such as TiO2 and on understanding the mechanism of TiO2 NP-induced nanotoxicity through the evaluation of biomarkers. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 47 publications
4
53
0
Order By: Relevance
“…Coating nanomaterials with PEG also increases ReticuloEndothelial System (RES) [21]. We have already shown that PEGylation of TiO 2 NPs reduces cytotoxity and inflammatory response [22]. The results suggested that PEGylation of TiO 2 NPs could reduce many cellular responses.…”
Section: Introductionmentioning
confidence: 88%
“…Coating nanomaterials with PEG also increases ReticuloEndothelial System (RES) [21]. We have already shown that PEGylation of TiO 2 NPs reduces cytotoxity and inflammatory response [22]. The results suggested that PEGylation of TiO 2 NPs could reduce many cellular responses.…”
Section: Introductionmentioning
confidence: 88%
“…Modifying the surface of nanoparticles with PEG not only prevents agglomeration but also renders nanoparticles resistant to protein adsorption and increases the in vivo circulation time and biocompatibility. 22 Ju et al 23 inferred that the low toxicity of PEG-coated QDs was due to PEG coating, which can inhibit reactive oxygen species generation on the surface of QDs. Our result also demonstrated that PEG could relieve the hepatotoxicity of ZnO QDs induced by oxidative stress.…”
mentioning
confidence: 99%
“…This is primarily accomplished by modifying the pH in the surrounding bulk fluid [27]. A second approach to promote stability is to coat the particles with neutral or electrostatically repulsive materials [25]. The coating approach may be pursued in applications where the suspension must have a neutral pH or if the suspension requires a pH that falls within a range that does not promote dispersion stability.…”
Section: D2 Deposition Method-specific Suspension Formulationsmentioning
confidence: 99%
“…Lebrette et al measured ζ-potentials greater in magnitude than -40mV for pH values greater than 7.5 and less than 2.5 [29]. TiO 2 powders with IEPs shifted to lower, acidic pH values have also been studied and show a corresponding shift down of the region of pH instability [25,30].…”
Section: D3 Nanoparticle Electro-chemistrymentioning
confidence: 99%